A simple method suitable to study de novo root organogenesis - Chen, Xiaodong; Qu, Yuliang; Sheng, Lihong; Liu, Jingchun; Huang, Hai; Xu, Lin (Frontiers in Plant Science, 2014)
De novo root organogenesis is the process in which adventitious roots regenerate from detached or wounded plant tissues or organs. In tissue culture, appropriate types and concentrations of plant hormones in the medium are critical for inducing adventitious roots. However, in natural conditions, regeneration from detached organs is likely to rely on endogenous hormones. To investigate the actions of endogenous hormones and the molecular mechanisms guiding de novo root organogenesis, we developed a simple method to imitate natural conditions for adventitious root formation by culturing Arabidopsis thaliana leaf explants on B5 medium without additive hormones. Here we show that the ability of the leaf explants to regenerate roots depends on the age of the leaf and on certain nutrients in the medium. Based on these observations, we provide examples of how this method can be used in different situations, and how it can be optimized. This simple method could be used to investigate the effects of various physiological and molecular changes on the regeneration of adventitious roots. It is also useful for tracing cell lineage during the regeneration process by differential interference contrast observation of -glucuronidase staining, and by live imaging of proteins labeled with fluorescent tags.